Pediatric lymphomatoid papulosis - a case report and management considerations - Michał Dec; Hubert Arasiewicz (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Lymphomatoid papulosis (LyP) is a rare cutaneous disorder, most commonly observed in adults, and its occurrence in the pediatric population is exceedingly rare. We present the case of an 6-year-old male patient who exhibited clinical and histopathological features consistent with LyP. The patient presented with multiple erythematous papules on the trunk and extremities, which were accompanied by mild pruritus. The lesions intermittently appeared, disappeared, and changed in morphology. No lymphadenopathy or systemic symptoms were noted. The histopathological examination revealed a dense infiltrate of atypical lymphocytes with cerebriform nuclei in the dermis. Immunohistochemical analysis confirmed CD30 expression in the infiltrating cells, supporting the diagnosis of LyP. Topical corticosteroids were administered to alleviate pruritus and inflammation, although only minimal symptomatic relief was achieved. The beneficial effects of narrowband ultraviolet B (UVB) 311 phototherapy were observed for a duration of four months. Nevertheless, following the cessation of treatment, the reappearance of both the nodular lesions and smaller papular lesions was observed. Consequently, a therapeutic regimen consisting of the administration of methotrexate at a dosage of 10 mg once per week was initiated. The treatment of LyP varies depending on the severity of the lesions and the patient's symptoms, treatment decisions need to be carefully weighed due to the relatively benign nature of the disease. The diagnosis of LyP in pediatric patients is challenging because of its rarity and potential confusion with malignant lymphomas. Histopathology and immunohistochemistry play a pivotal role in distinguishing LyP from more aggressive entities.